Parental Involvement in Education: Building Partnerships for Student Success and Well-being - Sri Haryanto (Education Studies and Teaching Journal (EDUTECH), 2024)
Parental involvement in education has become an increasingly relevant research topic in efforts to improve student success and well-being. A careful review of the literature and original research confirms that parental participation has a significant correlation with children's academic achievement. This research aims to explore valuable information about the role of parental involvement in education, as well as its impact on the partnership between schools and parents. The results show that parental involvement should be seen as an active collaboration, where both parties have responsibility in the educational process. This research also highlights the importance of strengthening relationships between parents and educational institutions to support students' academic and emotional growth. By prioritizing parental involvement in education, it is hoped that we can create a learning environment that supports student success in the future.